Letter - Sheffield Federated Trades and Labour Council, 8 May 1926 (Sheffield)
1926-05-08 "Letter - Sheffield Federated Trades and Labour Council, 8 May 1926" [g0095001.jpg], 8 May 1926, Sheffield Federated Trades and Labour Council Local Organisation